2003
DOI: 10.1179/016164103101201625
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell ependymoma with a lipidized component that developed in the thoracic spinal cord

Abstract: The authors report a case of clear cell ependymoma with a lipidized component that developed in the thoracic spinal cord. A 59-year-old man was admitted to the hospital with an itchy pain in the left forearm to the left anterior and lateral chest for the past three years. Neurological findings on admission included dissociated sensory disturbance below the C8 level and increased deep tendon reflex in both lower extremities. An MRI scan of the spinal cord revealed an intramedullary tumor with a longer diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…There were no anaplastic features in the other reported cases. However, Min and Scheithauer [2] reported that the biological malignancy of CCE was the same as that of other ependymomas and varied with individual cases, and that the MIB-1 staining index was required for evaluation of malignancy [8]. In our case, the proliferation index was 5% at the lowest point and 10% at the highest by MIB-1, and with this finding the tumor was suggested to have a tendency to anaplasia.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…There were no anaplastic features in the other reported cases. However, Min and Scheithauer [2] reported that the biological malignancy of CCE was the same as that of other ependymomas and varied with individual cases, and that the MIB-1 staining index was required for evaluation of malignancy [8]. In our case, the proliferation index was 5% at the lowest point and 10% at the highest by MIB-1, and with this finding the tumor was suggested to have a tendency to anaplasia.…”
Section: Discussionmentioning
confidence: 61%
“…Some authors [21, 22] did not observe any EMA-positive reaction, whereas some authors reported EMA-positive ependymomas [1, 5, 23, 24]. Neuronal markers including synaptophysin, neurofilaments, neuron-specific enolase and chromogranin A are usually negative [8,9,10]. However, some cases have neuron-specific-enolase-positive tumor cells [3, 4, 11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][7][8][9][10][11][12][13][14][16][17][18][19][20][23][24][25][26][27][28] CCE seems to have a predilection for the supratentorial region (supratentorial, 42; infratentorial, 16; spinal, 4) in contrast to the classical subtypes of ependymomas. The recurrence rate of CCE in all locations was about 60% during the follow-up period, [1][2][3][4][5][7][8][9][10][11][12][13][14][16][17][18][19][20][23][24][25][26][27][28] which is higher than other subtypes of ependymoma. 15) The clinical course of CCE was the worst among benign ependymomas, with a significantly higher expression of M...…”
Section: Discussionmentioning
confidence: 99%